The association between macrosomia and glucose, lipids and hormones levels in maternal and cord serum: a case-control study - Xinxin Xing; Yifan Duan; Jie Wang; Zhenyu Yang; Qingqing Man; Jianqiang Lai (BMC, 2024)
Abstract Background The formation of macrosomia is associated with excessive nutrition and/or unable to regulate effectively. This case-control study aims to explore the relationship between macrosomia and glucose, lipids and hormones levels in maternal and cord serum. Methods In the case-control study, 78 pairs of mothers and newborns were recruited who received care at one hospital of Hebei, China between 2016 and 2019. According to the birth weight (BW) of newborns, participants were divided into macrosomia group (BW ≥ 4000 g, n = 39) and control group (BW between 2500 g and 3999 g, n = 39). Maternal vein blood and cord vein blood were collected and assayed. All data were compared between the two groups. Unconditional logistics regression analysis was used to test the relationship between macrosomia and glucose, lipids and hormones in maternal and cord serum. Results In maternal and cord serum, the levels of leptin, leptin/adiponectin ratio (LAR), glucose and triglyceride (TG) in macrosomia group were higher than those in control group, and the levels of high-density lipoprotein cholesterol (HDL-C) were lower. The percentage of maternal glucose and lipids transfer to cord blood did not differ between the two groups. High levels of TG in maternal serum were positively correlated with macrosomia, and high levels of LAR, TG and glucose in cord serum were positively correlated with macrosomia. Conclusion In conclusion, the results of the current study, suggest that the nutrients and metabolism-related hormones in maternal and umbilical cord are closely related to macrosomia. During pregnancy, the nutritional status of pregnant women should be paid attention to and to obtain a good birth outcome.